Kajian Teknis Produktivitas Dan Efisiensi Kerja Belt Conveyor Dalam Pengiriman Limestone & Silicastone Ke Storage Indarung Pada Pt. Semen Padang Sumatera Barat - Fadhilla Elka Putri; Rijal Abdullah (Departemen Teknik Pertambangan FT UNP, 2018)
PT. Semen Padang has a 31-lane conveyor system for limestone transportation and 6 lanes for transport of silicastone delivered from 4 units of limestone crusher, 1 unit of mosher silica to 5 industrial plants. Belt conveyor at PT. Semen Padang has different sizes so that the capacity of each belt for the delivery of raw materials will differ according to the delivery path. Therefore, production capacity of conveyor belt will depend on its minimum production capacity. PT. Semen Padang in the long-term 5 years plan to increase production target of 12,300.00 tons in 2021. Thus, it is necessary a technical study and evaluation so that belt conveyor can be used. In this research, combined between theory with field data, so get problem solving approach. And the results of data processing will be analyzed for subsequent to be generated a recommendation. Based on the results of research conducted can be summed up some of the following. First, the minimum production capacity of conveyor belt in limestone delivery is 1,744,954 ton / hour and silicastone 1,484,922 ton / hour. Second, the design of a limestone delivery line is a new belt carry connecting A1J12C-6A1J07 and A1J12B-A4J13. Third, several anticipations in increasing production targets include: adding mosher silica to the pit limit area, crushing conveying need for maintenance before operation, decrease material size before entering the hopper. Keywords: Productivity, Work Efficiency, Belt Conveyor, Limestone, Silicastone